2019
DOI: 10.1159/000502952
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delayed Bleeding after Therapeutic Gastrointestinal Endoscopy in Patients Receiving Oral Anticoagulants: A Multicenter Retrospective Study

Abstract: Background/Aims: Delayed bleeding is among the adverse events associated with therapeutic gastrointestinal endoscopy. The aim of this study was to evaluate risk factors for delayed bleeding after gastrointestinal endoscopic resection in patients receiving oral anticoagulants as well as to compare the rates of occurrence of delayed bleeding between the oral anticoagulants used. Methods: We retrospectively analyzed a total of 772 patients receiving anticoagulants. Of these, 389 and 383 patients were receiving di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…These results suggest that the risk of delayed PPB is smaller in those taking DOAC than in those taking clopidogrel or warfarin. A Japanese study recently reported the delayed bleeding rate of therapeutic endoscopic procedures (including polypectomy, endoscopic mucosal resection [EMR], and endoscopic submucosal dissection [ESD]) for lesions of the esophagus (2.1%), stomach (15.4%), duodenum (0.4%), and colon (82.1%) 16 . According to their predominantly colonic procedure data, the delayed bleeding rate was not significantly different between patients taking warfarin or DOAC (13.8% vs. 9.5%, respectively), but endoscopic hemostasis was more frequently required in those taking warfarin than DOAC (12.0 vs. 6.9%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the risk of delayed PPB is smaller in those taking DOAC than in those taking clopidogrel or warfarin. A Japanese study recently reported the delayed bleeding rate of therapeutic endoscopic procedures (including polypectomy, endoscopic mucosal resection [EMR], and endoscopic submucosal dissection [ESD]) for lesions of the esophagus (2.1%), stomach (15.4%), duodenum (0.4%), and colon (82.1%) 16 . According to their predominantly colonic procedure data, the delayed bleeding rate was not significantly different between patients taking warfarin or DOAC (13.8% vs. 9.5%, respectively), but endoscopic hemostasis was more frequently required in those taking warfarin than DOAC (12.0 vs. 6.9%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In a large population-based retrospective study regarding any kind of GI bleeding in patients taking DOACs, apixaban showed a relatively lower risk of GI bleeding than did dabigatran or rivaroxaban 20 . On the other hand, apixaban showed a higher risk of bleeding than rivaroxaban according to a Japanese multicenter retrospective study focused on GI bleeding after therapeutic endoscopy for patients taking DOACs 16 . Our data did not show any difference in delayed PPB according to the type of DOACs, which may be due to our limited number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the full-text of the remaining 27 articles, a total of 19 studies were found to be ineligible for the inclusion criteria, and were excluded. Finally, eight studies 11 12 13 14 15 16 17 18 were included for the meta-analysis. Results of the study flow diagram are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All articles demonstrated the outcome, and five of these 11 12 13 14 15 reported no thrombotic events. Therefore, the meta-analysis was conducted using three studies 16 17 18 with a total of 1,085 patients (601 patients with warfarin and 484 patients with DOACs). No significant difference was found between the warfarin and DOACs groups (OR = 2.0, 95 % CI [0.32–12.39]), and there was no heterogeneity (I² = 0, P = 0.879) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Peri-endoscopic management with HBT is now becoming a controversial management decision with regards to its efficacy and safety. Numerous studies highlighted in this review have demonstrated that the use of HBT is associated with a two- to three-fold increased risk of PPB[ 7 , 41 , 142 ], while being non-superior in thromboembolic event prevention, compared to warfarin cessation without HBT[ 1 , 107 , 143 , 144 ]. This heightened risk of PPB associated with HBT has been shown in a range of endoscopic procedures, including EMR, ESD, polypectomy, EUS ± FNA and ERCP with sphincterotomy.…”
Section: Discussionmentioning
confidence: 99%